1993
DOI: 10.1097/00000658-199307000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival Curves of Gastric Cancer Patients After Surgery According to the UICC Stage Classification and the General Rules for Gastric Cancer Study by the Japanese Research Society for Gastric Cancer

Abstract: The UICC classification is better than the GRGCS for classifying gastric cancer in Japan. However, UICC stage I does not need to be subdivided into stages IA and IB, and stage IV should be further subdivided into stages IVA and IVB according to the surgery performed: IVA, gastrectomy, and IVB, bypass or exploratory surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 1 publication
2
23
1
Order By: Relevance
“…With a mature follow-up, the 2-year OS rate of this treatment was 43% (95% CI 29.4-56.1). This appeared to be better than the 2-year OS of 20-25% that was estimated from previous studies of stage IV GC patients treated with chemotherapy alone or with surgery and postoperative chemotherapy [2,3,6,22]. However, our study failed to show a survival benefit, because our threshold 2-year survival probability was estimated to be 35%.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…With a mature follow-up, the 2-year OS rate of this treatment was 43% (95% CI 29.4-56.1). This appeared to be better than the 2-year OS of 20-25% that was estimated from previous studies of stage IV GC patients treated with chemotherapy alone or with surgery and postoperative chemotherapy [2,3,6,22]. However, our study failed to show a survival benefit, because our threshold 2-year survival probability was estimated to be 35%.…”
Section: Discussioncontrasting
confidence: 77%
“…It is often diagnosed at an advanced stage. The prognosis of stage IV GC is poor (e.g., the 1-, 2-, and 5-year survival rates of stage IV GC are approximately 40, 20, and \10%, respectively [2,3]), even if patients are treated surgically.…”
Section: Introductionmentioning
confidence: 99%
“…The clinicopathologic staging was performed according to the TNM criteria 24 and were categorized into early (stage I-II) and advanced (stage III-IV) because these criteria are known to affect the 5-year survival significantly. 25,26 The histologic type of a gastric carcinoma was defined as being intestinal (glandular, cohesive, or solid), diffuse and mixed according to the Lauren classification, 27,28 and the degree of differentiation was graded according to the WHO classification. The location of the tumor was divided into the proximal (cardia and body) and distal (antrum) stomach.…”
Section: Imaging and Pathologic Diagnosismentioning
confidence: 99%
“…Noh et al (2005) reported that the 5-year survival rate of early gastric cancer without lymph node metastasis is 94.2% and that of early gastric cancer with lymph node metastasis is 87.3%. Nio et al (1993) reported a 5-year survival rate of 95% for N1 patients and 68.4% for N2 patients for early gastric cancers, and Miwa et al (1984) observed similar rates of 90% and 79%, respectively. Seto et al (1997) reported a 5-year survival rate of 74% for patients with >4 positive lymph nodes.…”
Section: Discussionmentioning
confidence: 95%